2021
DOI: 10.32598/jhnm.31.1.2022
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With the Quality of Health Services Provided by Public Hospitals in Rasht, Iran

Abstract: This article has no abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…According to the findings of the review, 32 studies exclusively utilized the Kano Model, while 10 papers employ not only Kano Model but also other models for quality improvement. Among them, 5 studies integrated Kano Model with the SERVQUAL Model (C. M. Chou et al, 2015; Gomez Martin et al, 2019; Lacerda et al, 2021; Mehrabian et al, 2021; Patel & Bhatt, 2017). In addition, three articles combined Kano Model with QFD (Chiou & Cheng, 2008; Kuo et al, 2011; Zhang Qunxiang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings of the review, 32 studies exclusively utilized the Kano Model, while 10 papers employ not only Kano Model but also other models for quality improvement. Among them, 5 studies integrated Kano Model with the SERVQUAL Model (C. M. Chou et al, 2015; Gomez Martin et al, 2019; Lacerda et al, 2021; Mehrabian et al, 2021; Patel & Bhatt, 2017). In addition, three articles combined Kano Model with QFD (Chiou & Cheng, 2008; Kuo et al, 2011; Zhang Qunxiang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 5 studies using Kano Model and the SERVQUAL Model, 3 papers (Gomez Martin et al, 2019; Mehrabian et al, 2021; Patel & Bhatt, 2017) first used the SERVQUAL Model to determine the gap between patients’ perceptions and expectations of healthcare quality, and then applied Kano Model to identify attributes that significantly influence patients’ satisfaction. Chou (2015) administered both the SERVQUAL questionnaire and Kano questionnaire simultaneously, subsequently identifying the priority service through data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis confirmed that before the pandemic the quality of services stated by the Iranian patients was placed at an acceptable level compared to other countries [56]. In general, prior research reported varied results in Iran [57][58][59][60][61]. Such difference findings may be related to study settings, the time of the study, sample size, and the participants' status in terms of socio-economics factors.…”
Section: Discussionmentioning
confidence: 97%
“…According to this model, service quality can be measured in five dimensions: Tangibles (the appearance of physical facilities, equipment, personnel, and communication materials), Responsiveness (the willingness to help customers and to provide prompt service), Assurance (the knowledge and courtesy of employees and their ability to convey trust and confidence), Reliability (the ability to perform the promised service dependably and accurately), and Empathy (the provision of caring, individualized attention to the customer) are examined [53]. Regarding the quality of hospital services, the findings of previous studies before and after the outbreak of COVID-19 have reported different levels of service quality and its dimensions status [54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…In the end, the results of the study demonstrated that there is a direct, statistically significant relationship between organizational agility and the quality of services in development NGOs. ( Mehrabian, F , et al, 2021) .…”
Section: Introductionmentioning
confidence: 99%